Notwendige Bedingung für das Überleben der Eurozone: Konsequente Demokratisierung - Hans-Jörg Beilharz (IUBH Internationale Hochschule, 2018)
– This article gives an overview to the history of the Eurozone crisis, its immediate causes and the stabilization measures that have been taken so far. It sheds light on the current situation and its immense risks. The existing reform proposals are discussed and categorized. A future scenario describes that permanent and structurally determined economic imbalances between Eurozone's core countries and southern countries are likely. Therefore, the economic survival of the currency area crucially depends on financial transfers and the assumption of financial liability in favor of Eurozone's south. However, one-sided transfers are only politically feasible in the long-run, if they are directly democratically legitimized. If not, the whole European political project could fail due to the conflict about the common currency .
urn:nbn:de:101:1-2018070514044119827814
Keywords: E61; E62; E63; F41; F42; 650; Eurozone crisis; Optimum Currency Areas; monetary and fiscal policy; financial instruments; institutions; political negotiations; democracy